PENGARUH MODAL INTELEKTUAL, UKURAN PERUSAHAAN DAN KUALITAS AKTIVA PRODUKTIF TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN - Mayang Sharfina; La Ane; Anggriyani Anggriyani (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2023)
The problem in this study is the economic crisis that has resulted in banking in Indonesia experiencing a slump where many banks were liquidated because they were unable to maintain their performance. This study aims to determine the effect of intellectual capital, company size, and quality of productive assets partially on the financial performance of banking companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The population in this study were 47 banking companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The sampling method used is purposive sampling, with a total sample of 13 companies, for 2017-2020 as many as 52 samples. Data collection techniques by downloading financial reports from the website www.idx.co.id. The data analysis technique used in this study uses multiple regression and hypothesis testing (t test and F test) .The results of this study partially indicate that intellectual capital has no significant effect on financial performance with a sig value of 0.275 > 0.05. Then the size of the company has significant effect on financial performance with a sig value of 0.013 < 0.05. While the quality of productive assets has a significant effect on financial performance with a sig value of 0.000 <0.05. Simultaneously, intellectual capital, company size and quality of productive assets affect the company's performance. The conclusion in this study is that intellectual capital and firm size have an effect on ROA. Meanwhile, the quality of earning assets has no effect on ROA.